Spontaneous triploidy and NOR activity in Eigenmannia sp. (Pisces, Sternopygidae) from the Amazon basin - De Almeida Toledo, L. F.; Foresti, F. [UNESP]; De Almeida Toledo Filho, S. (Springer Nature, 1985)
The occurrence of a natural triploid among diploid individuals of Eigenmannia sp from the Amazon basin is described. The diploid individuals had 2n=31 and 32 chromosomes, the difference in chromosome number being due to a Robertsonian rearrangement. The triploid individual presented 2n=46 and had two fused acrocentrics. NOR activity was present in the three homologues of triploid and a NOR polymorphism was detected in the triploid and diploids. © 1985 Dr W. Junk Publishers.